Alcohol consumption in adolescence is associated with a lower risk of multiple sclerosis in a Danish cohort. (October 2019) - Andersen, Christina; Søndergaard, Helle Bach; Bang Oturai, Ditte; Laursen, Julie Hejgaard; Gustavsen, Stefan; Larsen, Nanna Katrine; Magyari, Melinda; Just-Østergaard, Emilie; Thørner, Lise Wegner; Sellebjerg, Finn; Ullum, Henrik; Oturai, Annette Bang
Background and objective: Due to the possible existence of a vulnerable period of multiple sclerosis (MS) susceptibility in adolescence and because Danish teenagers have a high alcohol consumption, we investigated the association between alcohol consumption at ages 15–19 and the risk of developing MS. Methods: A total of 1717 patients with MS and 4685 healthy blood donors filled in a comprehensive environmental and lifestyle questionnaire. Data were analysed by logistic regression models and adjusted for selected confounders. Results: We found an inverse association between alcohol consumption in adolescence and risk of developing MS in both women ( p  < 0.001) and men ( p  = 0.012). Women with low alcohol consumption had an odds ratio (OR) of 0.56 (95% confidence interval (CI): 0.47–0.66) compared with non-drinking women. The ORs were similar for women with moderate (OR = 0.49, 95% CI: 0.38–0.62) and high consumption (OR = 0.57, 95% CI: 0.38–0.84). Men with low alcohol consumption had an OR of 0.69 (95% CI: 0.53–0.89) compared with non-drinking men but no decreased risk was found for men with moderate and high consumption. Conclusion: Alcohol consumption in adolescence was associated with lower risk of developing MS among both sexes.